The Balance Sheet As an Earnings Management Constraint (Case Study In Indonesia Manufacture Company) - Dwi Sudaryati (Journal of Accounting and Investment, 2012)
This research has the purpose to examine the balance sheet existence as an earnings management constraint. This research use the secondary which it is taken from the quarterly financial statement of manufacture companies listed on Indonesia Stock Exchange (IDX) during 2008-2009 periods. This research used 68 manufacture companies as its sample. Then, the obtained data has regression analyzed by Generalized Ordered Logit Model. The Output of regression indicates that there is significant relation between net assets with the earnings surprise. The reporting earnings surprise smaller negative or larger positive decrease when the value of net asset is overstated. So, it can be concluded that balance sheet is as an earnings management constraint.